Production without Empowerment: Work reorganization from the perspective of motor vehicle workers - Lewchuk, Wayne; Robertson, David (Capital & Class, 1997)
This paper examines the relationship between new forms of work organization and worker empowerment from the perspective of workers. The data is drawn from a survey of 5,635 Canadian automobile workers. Workers were asked questions about their work-load, health and safety conditions, empowerment, and relations with management. It examines what it is like to work in plants organized according to the principles of lean production and compares empowerment in lean plants and traditionally organized plants.

Abstracts / Résumés [40, Fall 1997] (Labour/Le Travail, 1997)
English/French abstracts of articles published in the issue.

Abstracts / Résumés [v.39, Spring 1997] (Labour/Le Travail, 1997)
English/French abstracts of articles published in the issue.

Index, Volume 39 (Spring/Printemps 1997) (Labour/Le Travail, 1997)

Publications: Committee on Canadian Labour History (Labour/Le Travail, 1997)
List of recent publications by the Committee.

Resúmenes = Abstracts [v. 52, no. 3, Summer 1997] (Relations industrielles / Industrial Relations, 1997)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Resúmenes [v, 52, no. 1, Winter 1997] (Relations industrielles / Industrial Relations, 1997)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Resúmenes [v. 52, no. 2, Spring 1997] (Relations industrielles / Industrial Relations, 1997)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

Resúmenes [v. 52, no. 4, Fall 1997] (Relations industrielles / Industrial Relations, 1997)
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

The Transformation of Italian Communism - Amyot, Grant (Labour / Le Travail, 1997)
The article reviews the book, "The Transformation of Italian Communism," by Leonard Weinberg.
Keywords: BOOKS – Reviews; Communism; ITALY; Nonfiction; TRANSFORMATION of Italian Communism; The (Book); WEINBERG; Leonard

Cold War Canada: The Making of a National Insecurity State, 1945-1957 - Avery, Donald Howard (Labour / Le Travail, 1997)
The article reviews the book, "Cold War Canada: The Making of a National Insecurity State, 1945-1957," by Reg Whitaker and Gary Marcuse.
Keywords: 1945-; BOOKS – Reviews; COLD War Canada: The Making of a National Insecurity State 1945-1957 (Book); Canada; History; MARCUSE; Gary; Nonfiction; WHITAKER; Reg

Prince of the People: The Life and Times of a Brazilian Free Man of Colour - Barman, Roderick J. (Labour / Le Travail, 1997)
The article reviews the book, "Prince of the People: The Life and Times of a Brazilian Free Man of Colour," by Eduardo Silva.
Keywords: BOOKS – Reviews; ETHNIC groups; Nonfiction; PRINCE of the People: The Life & Times of a Brazilian Free Man of Colour (Book); SILVA; Eduardo

A Dreamer's Paradise Lost: Louis C. Fraina/Lewis Corey (1892-1953) and the Decline of Radicalism in the United States - Barrett, Jim (Labour / Le Travail, 1997)
The article reviews the book, "A Dreamer's Paradise Lost: Louis C. Fraina/Lewis Corey (1892-1953) and the Decline of Radicalism in the United States," by Paul M. Buhle.
Keywords: BOOKS – Reviews; BUHLE; Paul M.; DREAMER'S Paradise Lost: Louis C. Fraina/Lewis Corey 1892-1953 & the Decline of Radicalism in the United States; A (Book); Nonfiction; Radicalism

D'un atelier de moulage à un autre: les migrations des mouleurs originaires des Forges du Saint-Maurice et la segmentation du marché du travail nord-américain, 1851-1884 - Bischoff, Peter C. (Labour / Le Travail, 1997)
Les migrations des mouleurs originaires des Forges du Saint-Maurice doivent être situées dans un marché du travail continental segmenté par les développements sectoriel et géographique de l'industrie, et par l'évolution du syndicalisme. Le déclin du secteur des haut fourneaux et l'essor concomitant des fonderies urbaines, amènent ces ouvriers à Montréal et dans d'autres villes du Québec. Attirés par des conditions de travail suprérieures, les mouleurs se rapprochent aussi graduellement du centre géographique de l'industrie: c'est-à-dire les villes du sud de l'Ontario et du nord-est des États-Unis. La filière migratoire communautaire constitue un instrument important pour leurs déplacements. Mais plusieurs mouleurs adhèrent également à l'Union internationale des mouleurs, et utilisent la filière migratoire syndicale, afin de pénétrer la portion du marché du travail contrôlée par cette organisation. Ces types demouvements témoignent des contraintes, mais aussi de l'ingéniosité des ouvriers dans un contexte de transformations socioéconomiques importantes. // The migrations of the moulders coming from the St. Maurice Forges must be situated in a context of labour market segmentation under the dual pressure of the industry's growth and geographical expansion, and the development of unionism. Because of the blast furnaces decline and the concomitant blossoming of urban foundries, these workers went to Montréal and other Québec cities. They also gradually moved to the industry's geographical center, attracted by better working conditions: the cities of south Ontario and the north-east of the United States. The community migratory network was an important tool for their travels. But many moulders also joined the Iron Moulders International Union, and used the union's migratory network, to get into the section of the labour market under the organization's control. These types of movements reveal the constraints, but also the ingenuity of workers, in a context of important socio-economical transformations.
Keywords: EMIGRATION & immigration; LABOR market; MARKET segmentation; Ontario; SOCIOECONOMICS; UNIONISM (Irish politics)

The Clothes Off Our Back: A History of ACTWU 459 - Black, Errol (Labour / Le Travail, 1997)
The article reviews the book,"The Clothes Off Our Back: A History of ACTWU 459," by Debra Lindsay.
Keywords: AMALGAMATED Clothing & Textile Workers Union; BOOKS – Reviews; CLOTHES off Our Back: A History of ACTWU 459; The (Book); LINDSAY; Debra; Nonfiction

Producing Power: Ethnicity, Gender, and Class in a Caribbean Workplace - Bolland, O. Nigel (Labour / Le Travail, 1997)
The article reviews the book, "Producing Power: Ethnicity, Gender and Class in a Caribbean Workplace," by Kevin A. Yelvington.
Keywords: BOOKS – Reviews; Ethnicity; Nonfiction; PRODUCING Power: Ethnicity; Gender & Class in a Caribbean Workplace (Book); YELVINGTON; Kevin A.

Les gestionnaires et la négociation - Bourque, Reynald (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "Les gestionnaires et la négociation," by David A. Lax and James K. Sebenius, édition française by Gilles Gauthier and Marie Thibault
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Negotiations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

The Canadian Auto Workers: The Birth and Transformation of a Union - Boyle, Kevin (Labour / Le Travail, 1997)
The article reviews the book, "The Canadian Auto Workers: The Birth and Transformation of a Union," by Sam Gindin.
Keywords: Automobile industry workers; BOOKS – Reviews; CANADIAN Auto Workers: The Birth & Transformation of a Union; The (Book); GINDIN; Sam; Nonfiction

The Making of Western Labor Radicals: Denver's Organized Workers, 1878-1905 - Bright, David (Labour / Le Travail, 1997)
The article reviews the book, "The Making of Western Labor Radicals: Denver's Organized Workers, 1878-1905," by David Brundage.
Keywords: BOOKS – Reviews; BRUNDAGE; David; MAKING of Western Labor Radicals: Denver's Organized Workers 1878-1905; The (Book); Nonfiction; RADICALS

Le Monde du travail au Québec: Bibliographie - Burgess, Joanne (Labour/Le Travail, 1997)
The article reviews the book, "Le Monde du Travail au Québec: Bibliographie = The World of Labour in Quebec: Bibliography," by James Douglas Thwaites and André Leblanc.

Thunder Bay: From Rivalry to Unity - Burley, David (Labour / Le Travail, 1997)
The article reviews the book, "Thunder Bay: From Rivalry to Unity," edited by Thorold J. Tronrud and A. Ernest Epp.
Keywords: BOOKS – Reviews; EPP; A. Ernest; History; Nonfiction; THUNDER Bay: From Rivalry to Unity (Book); TRONRUD; Thorold J.

The Secret World of American Communism - Carley, Michael Jabara (Labour / Le Travail, 1997)
The article reviews the book, "The Secret World of American Communism," by Harvey Klehr, John E. Haynes and Fridrikh I. Firsov.
Keywords: BOOKS – Reviews; Communism; FIRSOV; Fridrikh I.; HAYNES; John E.; KLEHR; Harvey; Nonfiction; SECRET World of American Communism; The (Book); United States

The Duty to Accomodate: Its Growing Impact on the Grievance Arbitration Process - Carter, Donald D. (Relations industrielles / Industrial Relations, 1997)
Grievance arbitrators now have a responsibility to interpret and apply human rights legislation in the course of resolving collective agreement disputes. This responsibility, however, raises the question of whether grievance arbitration is the most suitable forum for the application of human rights laws. In Canada, grievance arbitration has been a hybrid process, containing both public and private components. Recent arbitral jurisprudence, however, suggests that arbitrators see themselves as primarily private adjudicators. These cases indicate that arbitrators have been reluctant to give full scope to the duty to accommodate in order to avoid disturbing the terms of the collective agreement. This reluctance to play a full role as human rights adjudicators means that arbitration is not necessarily the most ideal forum for the enforcement of Canadian human rights laws.
Keywords: Arbitrators; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Collective bargaining; Court decisions; Grievance procedures; HUMAN rights; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Changing Work Systems, Changing Social Relations? A Canadian General Motors Plant - Clarke, Louise (Relations industrielles / Industrial Relations, 1997)
The paper presents findings of an ethnographic case study on social relations in an existing General Motors vehicle assembly plant where the traditional drag chain has been replaced by Swedish automated guided vehicle technology and some aspects of Japanese work organization have been implemented. The findings challenge claims that Fordism is being replaced by a fundamentally new production model, and that this is resulting in more fulfilling work and cooperative social relations. There are many fulfilling work and cooperative social relations. There are many continuities with Fordism and highly contradictory social relations. This and other studies of new work systems suggest, in fact, that contradictions between control and commitment, rather than being minimized or dissolved, can actually be heightened.
Keywords: AUTOMOBILE industry; Automation; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Case studies; Changes; Cooperation; Impact analysis; Labor Unions; Labor relations; Production management; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Stanley Bréhaut Ryerson, un intellectuel de combat - Claveau, Cylvie (Labour / Le Travail, 1997)
The article reviews the book, "Stanley Bréhaut Ryerson, un intellectuel de combat," edited by Robert Comeau and Robert Tremblay.

What Kind of Unionism: Struggles Among Sydney Steel Workers in the SWOC Years, 1936-1942 - Crawley, Ron (Labour / Le Travail, 1997)
In late 1936 steel worker activists in Sydney launched a new organizing drive at the plant under the auspices of the CIO's Steel Workers Organizing Committee (SWOC). This effort drew the support of steel workers in a way that previous organizing attempts had not. However, the militant and self-reliant traditions of the steel workers collided with the cautious strategies and bureaucratic practices of the appointed SWOC leadership in the United States and Canada. As steel workers at Sydney showed great solidarity in their struggle with DOSCO, they also resisted what they saw as undemocratic and highly accommodationist practices by the union's national and international leadership. The struggles within the union embraced the issues of Canadian autonomy and nationalism as well as rank-and-file union control and the democratic rights of union members. It amounted to a struggle over what type of unionism was to be established within the Canadian steel industry.
Keywords: Bureaucracy; Canada; IRON & steel workers; Leadership; STEEL Workers Organizing Committee (U.S.); Steel industry; United States

Grace Hartman: A Woman for her Time - Crowley, Terry (Labour / Le Travail, 1997)
The article reviews the book, "Grace Hartman: A Woman for her Time," by Susan Crean.
Keywords: BOOKS – Reviews; CREAN; Susan; GRACE Hartman: A Woman for Her Time (Book); HARTMAN; Grace; Nonfiction

Les vrais maîtres de la forêt québécoise - Cyr, Jean-Roch (Labour / Le Travail, 1997)
The article reviews the book, Les vrais maîtres de la forêt québécoise," by Pierre Dubois, preface by Richard Desjardins.

Sizing Down: Chronicle of a Plant Closing: With Lessons for Understanding and Survival - Dandaneau, Steven P. (Labour / Le Travail, 1997)
The article reviews the book, "Sizing Down: Chronicle of a Plant Closing: With Lessons for Understanding and Survival," by Louise Moser Illes.
Keywords: BOOKS – Reviews; DOWNSIZING of organizations; ILLES; Louise Moser; Nonfiction; SIZING Down: Chronicle of a Plant Closing: With Lessons for Understanding & Survival (Book)

Crossing The Line: Unionized Employee Ownership and Investment Funds - Dennie, Donald (Labour / Le Travail, 1997)
The article reviews the book, "Crossing The Line: Unionized Employee Ownership and Investment Funds," by Jack Quarter.
Keywords: BOOKS – Reviews; CROSSING the Line: Unionized Employee Ownership & Investment Funds (Book); Employee ownership; Nonfiction; QUARTER; Jack

Le syndicalisme contemporain et son avenir - Desmarais, Jacques (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "Le syndicalisme contemporain et son avenir," edited by Henryk Lewandowski and Zbigniew Hajn.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; International; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Gentle Rebel: Letters of Eugene V. Debs - Dick, W. M. (Labour / Le Travail, 1997)
The article reviews the book, "Gentle Rebel: Letters of Eugene V. Debs," edited by J. Robert Constantine.
Keywords: BOOKS – Reviews; CONSTANTINE; J. Robert; GENTLE Rebel: Letters of Eugene V. Debs (Book); Nonfiction; STRIKES & lockouts

Documents pour l'étude des expositions et musées pour la prévention des accidents et des maladies du travail au Québec au début du siècle - Dionne, Jean-Claude (Labour / Le Travail, 1997)
Public exhibitions about work safety assumed an importance for both workers and employers at the beginning of the 20th century that is difficult to evaluate from a late-20th-century perspective. In Quebec, Louis Guyon, chief inspector of industrial establishments and public edifices, noted with interest expositions in Germany and France. Through his efforts the first North American exposition concerning the prevention of accidents was inaugurated in Montreal on 23 September 1901. Only insufficient government funds prevented Guyon from following European models in creating a worker safety museum. Similarly, a worker health museum did not materialize in the province because of funding problems.

Unionization, Union Involvement, and the Performance If Gainsharing Programs - Dong-One, Kim; Voos, Paula B. (Relations industrielles / Industrial Relations, 1997)
A study empirically examines the relationships between union status, union involvement, and the performance of gainsharing programs. The predictions of various competing theoretical perspectives are evaluated: 1. the agency/transaction cost approach, 2. the monopoly model, 3. the institutional voice model, and 4. a 2-faces model of labor organization. Gainsharing programs with union involvement in program administration resulted in better perceived performance than average programs in the nonunion sector. However, gainsharing programs in the union sector without union involvement had worse outcomes than those in the nonunion sector. These 2 divergent situations resulted in union status itself having an insignificant relationship with program performance.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Effects; Gainsharing; Labor Unions; Profit sharing plans; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Unionization

Wild Things: Nature, Culture and Tourism in Ontario, 1790-1914 - Dubinsky, Karen (Labour / Le Travail, 1997)
The article reviews the book, "Wild Things: Nature, Culture and Tourism in Ontario, 1790-1914," by Patricia Jasen.
Keywords: BOOKS – Reviews; JASEN; Patricia; Nonfiction; Ontario; WILD Things: Nature; Culture & Tourism in Ontario 1790-1914 (Book)

Hard Lessons: The Mine Mill Union in the Canadian Labour Movement - Dunk, Thomas (Labour / Le Travail, 1997)
The article reviews the book, "Hard Lessons: The Mine Mill Union in the Canadian Labour Movement," edited by Mercedes Steedman, Peter Suschnigg and Dieter K. Buse.
Keywords: BOOKS – Reviews; BUSE; Dieter K.; HARD Lessons: The Mine Mill Union in the Canadian Labour Movement (Book); Labor movement; Nonfiction; STEEDMAN; Mercedes; SUSCHNIGG; Peter

White Guys: Studies in Post-Modern Domination and Difference - Dunk, Thomas (Labour / Le Travail, 1997)
The article reviews the book, "White Guys: Studies in Post-Modern Domination and Difference," by Fred Pfeil.
Keywords: BLACK white differences; BOOKS – Reviews; Nonfiction; PFEIL; Fred; WHITE Guys: Studies in Post-Modern Domination & Difference (Book)

The Invention of White Race, Volume 1: Racial Oppression and Social Control - Eltis, David (Labour / Le Travail, 1997)
The article reviews the book, "The Invention of White Race: Racial Oppression and Social Control," Volume 1, by Theodore W. Allen.
Keywords: ALLEN; Theodore W.; BOOKS – Reviews; CAUCASIAN race; INVENTION of White Race: Racial Oppression & Social Control (Book); Nonfiction

Roaring Days: Rossland's Mines and the History of British Columbia - Emmons, David M. (Labour / Le Travail, 1997)
The article reviews the book, "Roaring Days: Rossland's Mines and the History of British Columbia," by Jeremy Mouat.
Keywords: BOOKS – Reviews; British Columbia; History; MOUAT; Jeremy; Nonfiction; ROARING Days: Rossland's Mines & the History of British Columbia (Book)

Highwire Act: Power, Pragmatism, and the Harcourt Legacy - Epp, A. Ernest (Labour / Le Travail, 1997)
The article reviews the book, "Highwire Act: Power, Pragmatism, and the Harcourt Legacy," by Daniel Gawthrop.
Keywords: BOOKS – Reviews; GAWTHROP; Daniel; HIGHWIRE Act: Power; Pragmatism & the Harcourt Legacy (Book); Nonfiction; PRAGMATISM

'Ruffled' Mistresses and 'Discontented' Maids: Respectability and the Case of Domestic Service, 1880-1914 - Fahrni, Magda (Labour / Le Travail, 1997)
Domestic service was an institution of considerable importance for working-class women and middle-class householders in Canada between 1880 and 1914. Service was instrumental in shaping class relations, in large part because it brought the working class directly into the bourgeois home. It was thus an arena where bourgeois and working-class versions of respectability met, and sometimes clashed. Service was essential to the elaboration of a respectable bourgeois lifestyle, and was considered a satiable occupation for working women, yet the peculiar restrictions of the occupation ensured that domestics would often find the trappings of respectability difficult to maintain. Domestics walked a fine line between 'respectability' and 'deviance'; indeed, in the eyes of many, service was an institution that straddled this line.
Keywords: Canada; HOUSEHOLD employees; LIFESTYLES; Stockholders; Women employees; Working class

Wives and Mothers, Schoolmistresses and Scullery Maids: Working Women in Upper Canada, 1790-1840 - Fingard, Judith (Labour / Le Travail, 1997)
The article reviews the book, "Wives and Mothers, Schoolmistresses and Scullery Maids: Working Women in Upper Canada, 1790-1840," by Elizabeth Jane Errington.
Keywords: BOOKS – Reviews; Canada; ERRINGTON; Elizabeth Jane; Nonfiction; WIVES & Mothers; Schoolmistresses & Scullery Maids: Working Women in Upper Canada 1790-1840 (Book); WOMEN – Employment

Seeking the Highest Good: Social Service and Gender at the University of Toronto, 1888-1937 - Finkel, Alvin (Labour / Le Travail, 1997)
The article reviews the book "Seeking the Highest Good: Social Service and Gender at the University of Toronto, 1888-1937," by Sara Z. Burke.
Keywords: BOOKS – Reviews; BURKE; Sara Z.; Nonfiction; SEEKING the Highest Good: Social Service & Gender at the University of Toronto 1888-1937 (Book); Social services

The Union Inspiration in American Politics: The Autoworkers and the Making of a Liberal Industrial Order - Fones-Wolf, Elizabeth (Labour / Le Travail, 1997)
The article reviews the book, "The Union Inspiration in American Politics: The Autoworkers and the Making of a Liberal Industrial Order," by Stephen Amberg.
Keywords: AMBERG; Stephen; AUTOMOBILE industry workers – United States; BOOKS – Reviews; Nonfiction; UNION Inspiration in American Politics: The Autoworkers & the Making of a Liberal Industrial Order; The (Book)

Securing the Male Breadwinner: A Feminist Interpretation of PC 1003 - Forrest, Anne (Relations industrielles / Industrial Relations, 1997)
It is argued that labor's rights have been effectively the rights of working-class men because only men were constructed as family breadwinners for whom collective bargaining was both necessary and legitimate. Working-class women, by contrast, were defined as non-working wives and mothers, so had no claim to steady jobs at good wages or to union representation in their own right. Secondly, PC 1003 accorded rights to men (but not women) inasmuch as it codified an industrial model of workers' rights. Thirdly, PC 1003 supported and encouraged the growth of a male model of collective bargaining. The implications of a gendered analysis of PC 1003 for the study of industrial relations are discussed.
Keywords: Blue collar workers; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Collective bargaining; Employees; Employment; Gender; Labor Unions; Labor law; Labor relations; Rights; Sexes; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Women

The Labour Stamp: The Image of the Worker on Canadian Postage Stamps - Frank, David (Labour / Le Travail, 1997)
Introduces Canadian postage stamps as a form of public identity, memory and iconography, and applies this lens to the representation on stamps of workers and the labour movement. Analyzes the particular stamps where workers and labour are commemorated, reproductions of which are included are in the article. Compares the relatively small number of Canadian labour stamps to those produced in the UK, Australia, France, and the US. Concludes that there should be greater inclusion of workers and unions in the selection and design of stamps, as recommended by the Canadian Committee on Labour History to Canada Post.
Keywords: Canada; Employees; FRANK; David; LABOUR/LE Travail (Book); NATIONAL characteristics; POSTAGE stamps; WRITING About Canada (Book); Women employees

The Revolution Deferred: The Painful Birth of Post-Apartheid South Africa - Freund, William (Labour / Le Travail, 1997)
The article reviews the book, "The Revolution Deferred: The Painful Birth of Post-Apartheid South Africa," by Martin J. Murray.
Keywords: APARTHEID; BOOKS – Reviews; MURRAY; Martin J.; Nonfiction; REVOLUTION Deferred: The Painful Birth of Post-Apartheid South Africa (Book); SOUTH Africa

Labour and Unions in a Period of Transition - Gani, Abdul (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "Labour and Unions in a Period of Transition," edited by C. S. Venkata Ratnam, Gerd Botterweck and Pravin Sinha.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Roles; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Gender-Based Wage Differences: The Effects of Occupation and Job Segregation in Israel - Gattiker, Urs E.; Cohen, Aaron (Relations industrielles / Industrial Relations, 1997)
A study examines gender differences in the process governing salary disparity between typically female occupations and typically male occupations. The findings indicate that choice of occupation does affect income disparity. The study provides evidence of pay discrimination against men in predominantly female occupations and against women in female- and male-dominated positions. Women did not experience a positive effect by being employed in the public sector, nor did either of the genders working in larger organizations. The implications of the findings for the generalizability of human capital, structural and institutional theories explaining wage disparity in a cross-national context are discussed.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Gender; Labor Unions; Sex discrimination; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Wage differential; Wages & salaries

La sous-traitance forestière dans le Nord-Est ontarien, 1900-1930 - Gaudreau, Guy (Labour / Le Travail, 1997)
Cet article dresse un portrait des sous-traitants forestiers à l'oeuvre dans le nord-est Ontarien au cours des premières décennies du XXe siècle. À partir d'une source méconnue, les registres forestiers gouvernement aux des districts de Sudbury et de North Bay, Ontario, l'auteur suit l'évolution de 269 sous-traitants échantillonnés. La durée et l'emplacement de leurs activités, leur ethnicité, les volumes et la nature des contrats obtenus, et le nombre d'entreprises avec lesquelles ils font affaires, constituent les variables majeures de cette étude. Bien que la précarité économique ne fasse pas de doute sur certains plans, notamment par l'obligation qui leur est imposée de déménager sans cesse leurs activités et par les fréquentes interruptions de leurs affaires, elle paraît, en bout de course, avoir été exagérée par l'historiographie. En effet, la situation économique des papetières de la région n'est guère plus reluisante que celle des sous-traitants, sans compter que le mode d'attribution des permis de coupe ontariens autorise la présence de plusieurs autres entreprises forestières régionales, de telle sorte qu'il n'y a pas de monopoles régionaux comme c'est le cas au Québec et au Nouveau-Brunswick. En outre, les sous-traitants font preuve dans les contrats obtenus d'une étonnante capacité d'adaptation.
Keywords: CONTRACTS; Contract labor; FORESTERS; Literature; New Brunswick; Ontario; QUEBEC (Province)

Managerial Strategies, Labour and Employment Relations and the State: The Canadian Case and Beyond - Godard, John (British Journal of Industrial Relations, 1997)
This paper addresses: (1) the extent to which changes appear to have occurred in managerial strategies and labour and employment relations in Canadian firms, and (2) the role of the state relative to anonymous economic forces in accounting for Canadian developments. The general findings are that, while there have been a number of significant changes, these have been more moderate than expected by ‘transformation’ theory; furthermore, the Canadian case is consistent with the argument that state actions play a major role relative to more anonymous economic ‘forces’ in accounting for developments in labour and employment relations. It also suggests an alternative model to that typically assumed by transformation theory, one in which state policies and economic conditions are considered to be important not only for their direct effects on employer policies, but also for their indirect effects, through their implications for worker expectations and union militancy. Although these conclusions are tentative and call for more systematic, comparative research, they are consistent with arguments by Burawoy and others that state actions can serve as an important source of labour regulation at the level of the firm.
http://onlinelibrary.wiley.com/doi/10.1111/1467-8543.00061/abstract

Histoire de l'Abitibi-Témiscamingue - Goulet, Denis; Hudon, Christine; Lanthier, Pierre (Labour / Le Travail, 1997)
The article reviews the book, "Histoire de l'Abitibi-Témiscamingue," edited by Odette Vincent.

Crewe: Railway Town, Company and People, 1840-1914 - Green, David R. (Labour / Le Travail, 1997)
The article reviews the book, "Crewe: Railway Town, Company and People, 1840-1914," by Diane K. Drummond.
Keywords: BOOKS – Reviews; CREWE (England); CREWE: Railway Town; Company & People 1840-1914 (Book); DRUMMOND; Diane K.; England; Nonfiction

Internal Versus External Labour Flexibility: A Two-Plant Comparison in Canadian Manufacturing - Grenier, Jean-Noël; Giles, Anthony; Bélanger, Jacques (Relations industrielles / Industrial Relations, 1997)
The article examines the divergent patterns of labor flexibility in 2 Canadian power transformer plants owned by the same company and producing similar products with identical technologies. The case study results are used to point to 3 over-simplifications in the flexibility debate: 1. the claim that "numerical" and "functional" flexibility are incompatible, 2. the argument that North American management relies more heavily on external flexibility than on flexibility, and 3. the widespread contention that the traditional collective agreement is the chief barrier to achieving a more flexible organization of production in North America.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Comparative analysis; Electric utilities; Flexibility; Labor; Labor Unions; Labor relations; Manufacturers; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies

Les pratiques d'aide à l'équilibre emploi-famille dans les organisations du Québec - Guérin, Gilles; St-Onge, Sylvie; Haines, Victor; Trottier, René; Simard, Manon (Relations industrielles / Industrial Relations, 1997)
La problématique de l'équilibre emploi-famille (ÉEF) est de plus en plus au cœur des préoccupations organisationnelles, à tel point que se développe l'idée qu’il faut gérer cet équilibre, c'est-à-dire plus explicitement qu'il faut implanter ou modifier certaines pratiques de gestion pour aider les employés à surmonter leurs problèmes d'ÉEF. Cette recherche, effectuée auprès de 301 organisations ayant des opérations au Québec, vise à répondre aux questions suivantes : (1) Quel est le degré d'implantation au Québec des diverses pratiques présentées dans la littérature spécialisée ? (2) Sous quelles formes ces pratiques sont-elles implantées ? (3) Quelles sont les organisations qui les ont implantées ? (4) Quels sont leurs effets ? et finalement (5) Existe-t-il à proprement parler des programmes d'aide à l'équilibre emploi-famille dans les organisations québécoises ?
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Corporations; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Work & family

L'efficacite des pratiques de gestion des ressources humaines: le cas de la gestion des professionels syndiques au Quebec - Guérin, Gilles; Wils, Thierry; Lemire, Louise (Relations industrielles / Industrial Relations, 1997)
Le malaise professionnel — vu comme un conflit entre les valeurs professionnelles et les exigences organisationnelles — a donné lieu à une abondante littérature au cours des quarante dernières années. Le concept est ici repris dans le but d'élaborer un construit qui s'appuie sur les huit principaux points de tension entre les cadres et les professionnels, soit la nature du travail, l'autonomie, la participation à la prise de décision, le style de gestion du supérieur, les conditions de travail, le développement de carrière, la reconnaissance et l'éthique. Construit à partir de questions mesurant tant les attentes professionnelles que les perceptions de réalisation de 2497 professionnels syndiqués du Québec, le construit de 16 indicateurs se révèle cohérent et valide puisqu'il est significativement corrélé avec les attitudes et comportements généralement associés au malaise par les auteurs.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Human resource management; Labor Unions; Professions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Impact or Layoff Announcements on the Market Value of the Firm - Gunderson, Morley; Verma, Anil; Verma, Savita (Relations industrielles / Industrial Relations, 1997)
A study examines the effect of layoff announcements on the market's valuation of firms. The event study methodology is applied to a sample of 214 announcements of layoffs made by major Canadian firms that traded on the Toronto Stock Exchange over the period 1982-1989. The main results are: 1. The market responds to the news of layoffs in a negative fashion, lowering the value of firms that announce layoffs. 2. Almost all of the negative response occurs on the day of the announcement, suggesting that the market is not able to fully anticipate the new information, but that it responds to it very quickly.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Effects; Labor Unions; Layoffs; Securities; Securities markets; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Stock prices; Studies; Valuation

Debunking the Public Health Myth: Municipal Politics and Class Conflict During the Galt, Ontario Waterworks Campaigns, 1888-1890 - Hagopian, John S. (Labour / Le Travail, 1997)
This article refutes the assertion that the Galt, Ontario waterworks was built for public health reasons. The two Galt waterworks campaigns (1888 and 1890) are studied in the context of other contemporaneous local events, the most important of which was a moulders' strike in 1889. Popular resistance to businessmen's wants and public support for the striking moulders prompted the formation of a local board of trade and the threat of an industrial exodus from town. The waterworks authorization of 1890 resulted from the victory by buinessmen in this overt class stuggle. The development of Galt's waterworks reflected economic and political interests far more than public health concerns. The findings refut McLaughlin, and illustrate a novel connection between urban politics, infrastructure development, labour rleations, and industrial capitalism.
Keywords: BUSINESSMEN; Capitalism; Industrial relations; POLITICAL doctrines; Public health; WATERWORKS

Évolution de la pratique de la gestion des ressources humaines: une analyse de contenu d'annonces de presse (1975-1985-1995) - Haines, Victor; Arcand, Michel (Relations industrielles / Industrial Relations, 1997)
Si, au niveau du discours, la gestion des ressources humaines semble avoir développé de nouvelles approches, qu'en est-il réellement dans la pratique ? Par l'entremise d'une analyse de contenu d'annonces de presse, cette étude retrace l'évolution de certaines dimensions de la pratique de la gestion des ressources humaines entre 1975 et 1995. Les résultats indiquent que la pratique a connu une évolution qui requiert de nouvelles exigences professionnelles.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

New Deals: Business, Labor, and Politics in America, 1920-1935 - Hamilton, David E. (Labour / Le Travail, 1997)
The article reviews the book, "New Deals: Business, Labor and Politics in America, 1920-1935.," by Colin Gordon.
Keywords: BOOKS – Reviews; BUSINESS & politics; GORDON; Colin; NEW Deals: Business; Labor & Politics in America 1920-1935 (Book); Nonfiction; United States

The Economics of the Trade Union - Heery, Edmund (Labour / Le Travail, 1997)
The article reviews the book, "The Economics of the Trade Union," by Alison L. Booth.
Keywords: BOOKS – Reviews; BOOTH; Alison L.; ECONOMICS of the Trade Union; The (Book); Labor Unions; Nonfiction

Desert Capitalism: Maquiladoras in North America's Western Industrial Corridor - Hellman, Judith Adler (Labour / Le Travail, 1997)
The article reviews the book, "Desert Capitalism: Maquiladoras in North America's Western Industrial Corridor," by Kathryn Kopinak.
Keywords: BOOKS – Reviews; Capitalism; DESERT Capitalism: Maquiladoras in North America's Western Industrial Corridor (Book); KOPINAK; Kathryn; Nonfiction

Pathways to Change: Case Studies of Strategic Negotiations - Hercus, Terry (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "Pathways to Change: Case Studies of Strategic Negotiations," by Joel Cutcher-Gershenfeld, Robert B. McKersie and Richard E. Walton.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Collective bargaining; Labor Unions; Labor relations; Negotiations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

September 1931: A Re-Interpretation of the Royal Canadian Mounted Police's Handling of the 1931 Estevan Strike and Riot - Hewitt, Steve (Labour / Le Travail, 1997)
Reassesses the 1931 Estevan miners' strike and riot in light of internal RCMP reports recently released under the federal Access to Information Act. Discusses reporting by local police officials at the time, which was more nuanced and sympathetic to the miners than had previously been believed. However, the RCMP was also under heavy pressure from higher authorities and mine owners to crack down. Three miners were killed (one died in hospital) and eight others injured by the police in a violent confrontation on September 29, 1931. A photograph is reproduced of the common grave where the three miners were buried under the epitaph, "Murdered by RCMP."
Keywords: ESTEVAN (Sask.); HEWITT; Steve; LABOUR/LE Travail (Book); Miners; ROYAL Canadian Mounted Police; Riots; SASKATCHEWAN; STRIKES & lockouts

Relations professionnelles, conventions, régulations : pour prolonger le projet néoréaliste - Hoang-Ngoc, Liêm (Relations industrielles / Industrial Relations, 1997)
L'auteur rappelle d'abord les pistes tracées par les travaux néoréalistes en relations industrielles, puis il propose une perspective se situant dans le cadre d'une hétérodoxie institutionnaliste française afin de prolonger cette perspective. Après avoir distingué au sein du rapport salarial les règles organisationnelles et les règles institutionnelles, il porte son attention sur le système de relations professionnelles défini comme l'ensemble des règles institutionnelles. Il développe ensuite une hypothèse d'endogénéité relative des règles de contenu du système de relations professionnelles vis-à-vis des régimes d'accumulation. Puis il élabore une typologie qui met en évidence le type de relations professionnelles qui favorise l'enchaînement macroéconomique propre à chaque régime d'accumulation. Enfin, il considère les différences nationales qui sont mises sur le compte de la capacité exogène des acteurs, dotés d'une rationalité procédurale, à mettre en phase dans le temps les règles du système de relations professionnelles avec la régulation en place, d'où la possibilité de fortes marges d'indétermination. // Three perspectives that have emerged from neorealist studies in industrial relations are explored. An initial analytical contribution of the paper is to hierarchize the various categories of rules, particularly by distinguishing procedural rules from content rules and labor relations rules from human resource management rules. Through the concept of the system of rules, the paper examines the national character of rules located in a single economic space and examines the interaction of these rules with this space. Strategies pursued by collective actors are identified.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Collective bargaining; Labor Unions; Labor relations; R&D; Research & development; Rules; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Sexual Orientation and the Canadian Labour Movement - Hunt, Gerald (Relations industrielles / Industrial Relations, 1997)
The response of the Canadian labor movement to sexual orientation discrimination has been mixed and uneven. The Canadian Labour Congress, along with several provincial federations and a growing number of unions, have taken a leadership role in promoting equal rights for gays and lesbians, while other labor organizations have done nothing at all. Public sector and Canadian-based unions are much more likely to have been active than have American-based unions, even though there are important exceptions to these trends. These developments are partially explained by regional dynamics, membership demographics, degree of activism, the presence of women's committees, and organizational leadership.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Collective bargaining; Discrimination; Employment discrimination; Gays & lesbians; Labor Unions; Manycompanies; Polls & surveys; Ratings & rankings; Rights; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Statistical data

The Fabrication of Labor: Germany and Britain, 1640-1914 - Huzel, James P. (Labour / Le Travail, 1997)
The article reviews the book, "The Fabrication of Labor: Germany and Britain, 1640-1914," by Richard Biernacki.
Keywords: BIERNACKI; Richard; BOOKS – Reviews; FABRICATION of Labor: Germany & Britain 1640-1914; The (Book); Labor; Nonfiction

La géométrie du syndicalisme : une analyse comparative des identités et des idéologies - Hyman, Richard (Relations industrielles / Industrial Relations, 1997)
Cet article offre un cadre pour l'analyse comparative des orientations politiques des syndicats, en distinguant des types idéaux idéologiques et identitaires qui se rapportent, premièrement, à la négociation sur le marché du travail ; deuxièmement, au renforcement de l'intégration des travailleurs dans la société ; troisièmement, à la poursuite conflictuelle d'intérêts de classe. L'argument est qu'en pratique les mouvements syndicaux européens ont généralement épousé une combinaison de ces orientations dans laquelle deux des trois éléments ont été retenus (souvent de façon contradictoire) comme prioritaires. Les cas de la Grande-Bretagne, de l'Italie et de l'Allemagne sont utilisés pour démontrer différentes combinaisons d'idéologies et d'objectifs, et également pour révéler comment les identités héritées ont récemment été mises sous tension.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Editor's Note = Note du directeur [39, Spring 1997] - Iacovetta, Franca; Quinlan, Michael; Kealey, Gregory S. (Labour/Le Travail, 1997)
A letter to the editor is presented in response to the article "Immigration and Labour: Australia and Canada Compared" published in "Labour/Le Travail."
Keywords: LETTERS to the editor; Labor

The Struggle for the Breeches: Gender and the Making of the British Working Class - Jacobs, Ellen (Labour / Le Travail, 1997)
The article reviews the book, "The Struggle for the Breeches: Gender and the Making of the British Working Class," by Anna Clark.
Keywords: BOOKS – Reviews; CLARK; Anna; England; Nonfiction; STRUGGLE for the Breeches: Gender & the Making of the British Working Class; The (Book); Working class

Workers and Working Classes in the Middle East: Struggles, Histories, Historiographies - Kayali, Hasan (Labour / Le Travail, 1997)
The article reviews the book, "Workers and Working Classes in the Middle East: Struggles, Histories, Historiographies," by Zachary Lockman.
Keywords: BOOKS – Reviews; LOCKMAN; Zachary; Nonfiction; WORKERS & Working Classes in the Middle East: Struggles; Histories; Historiographies (Book); Working class

Editor's Note = Note de directeur [40, Fall 1997] - Kealey, Gregory S.; Palmer, Bryan D. (Labour/Le Travail, 1997)
Bryan Palmer is succeeding Gregory Kealey, who is stepping down as editor after 21 years. Mark Leier is succeeding Palmer as the book review editor; Palmer had held the post for nearly 15 years. In turn, Andrew Parnaby and Richard Rennie are the new co-editors of the Notebook, succeeding Leier. Andrée Lévesque continues as the French book review editor. Various editorial board changes are noted. As incoming editor, Palmer offers a reflection on the journal and its path forward.
Keywords: Editors; Labor; Retirement

E.P. Thompson-Objections and Oppositions - Kirk, Neville (Labour / Le Travail, 1997)
The article reviews the book, "E. P. Thompson-Objections and Oppositions," by Bryan D. Palmer.
Keywords: BOOKS – Reviews; E.P. Thompson-Objections & Oppositions (Book); Nonfiction; PALMER; Bryan D.; THOMPSON; E. P. (Edward Palmer); 1924-1993

Loyautés organisationnelle et professionnelle et choix de carrière : le cas des professionnels en ressources humaines au Québec - Labelle, Christiane; Guérin, Gilles; Wils, Thierry (Relations industrielles / Industrial Relations, 1997)
Cette étude, réalisée auprès de 1 133 professionnels en ressources humaines au Québec, a identifié, au moyen d'une analyse typologique des loyautés professionnelle et organisationnelle, trois groupes de professionnels. Plusieurs différences de perception concernant les facteurs de remise en question de la carrière ont servi conjointement avec d'autres variables sociodémographiques et de carrière à distinguer et nommer ces trois types de professionnels. Il s'agit des « professionnels établis », « en voie d'être établis » et « non établis ». Une discussion replace ces résultats dans le contexte du renouvellement de la fonction « ressources humaines » qui influence non seulement les tâches et rôles des professionnels du domaine, mais aussi certaines facettes de leur carrière.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Human resource managers; Labor Unions; Professions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Restructuration d'une direction de ressources humaines : le point de vue des acteurs - Labelle, Christiane; Wils, Thierry (Relations industrielles / Industrial Relations, 1997)
Depuis quelques années, les services de ressources humaines font l'objet de vives critiques, et ce, dans un contexte de ressources de plus en plus rares. Une façon de contrer cette menace de l'environnement est de « faire les choses autrement » en se structurant différemment. Par exemple, il est possible de passer d'une structure par fonctions (avec des spécialistes) à une structure par équipes multidisciplinaires (avec des généralistes). Le but de cette étude est d'évaluer dans quelle mesure cette nouvelle forme de structuration — par équipes multidisciplinaires — d'une direction de ressources humaines (DRH) a un impact sur les acteurs touchés par cette réorganisation (gestionnaires et membres de la DRH). Inspirées principalement de l'approche de l'évaluation des DRH par les clients, deux enquêtes par questionnaires ont été réalisées dans une organisation du secteur public. A partir d'un échantillon de 138 individus (79 gestionnaires et 59 membres de la DRH), l'analyse statistique révèle que la restructuration est perçue plus positivement par les gestionnaires que par les membres de la DRH.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

L'indemnisation des victimes d'accidents du travail et des maladies professionnelles : aspects juridiques en droit québécois - Laflamme, Anne-Marie (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "L'indemnisation des victimes d'accidents du travail et des maladies professionnelles : aspects juridiques en droit québécois," by Michel Sansfaçon.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Laws & regulations; Occupational health & safety; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Age-Related Injuries Among Male and Female Assembly Workers: A Study in the Swedish Automobile Industry - Laflamme, Lucie (Relations industrielles / Industrial Relations, 1997)
A study investigates whether there is evidence of age-related impairment in injury occurrence among assemblers in the Swedish automobile industry. A retrospective analysis of injuries sustained by male and female assemblers over a 10-year period was conducted, employing 5 age categories divided in to 10 yearly strata and 3 time periods. Age-related injury ratios (IR) were calculated for all injuries. Contrary expectation, IRs for older assemblers were generally low while consistently high IRs were recorded for younger assemblers, and for both male and female workers.
Keywords: AUTOMOBILE industry; Accidents; Age; Age and employment; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Correlation analysis; Industrial accidents; Labor Unions; Occupational accidents; Occupational safety; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies

Droits et conditions de travail des employés des agences de location de main-d'oeuvre - Laflamme, Roch; Carrier, Dany (Relations industrielles / Industrial Relations, 1997)
Un contexte économique difficile, des besoins de ressources humaines de plus en plus flexibles et une offre accrue de main-d’œuvre ont contribué à l'émergence de nouvelles formes d'emploi à temps partiel ou temporaire, souvent comblées par des agences de location de main-d’œuvre temporaire. Cet article cherche à présenter les conséquences pratiques qu'entraîne une relation d'emploi tripartite, employeur/salarié/agence, sur les droits et les conditions de travail des employés des agences de location de main-d’œuvre temporaire.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Contract labor; Labor Unions; Labor law; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Temporary employment

La part des militants: Biographie et mouvement ouvrier - Lagana, Marc (Labour / Le Travail, 1997)
The article reviews the book, "La part des militants: biographie et mouvement ouvrier," by Michel Dreyfus and Claude Pennetier.

Worker's Control on the Railroad: A Practical Example "Right Under Your Nose" - Lamonde, Fernande; Cameron, Nancy (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "Worker's control on the railroad: a practical example 'right under your nose,'" edited by by G.R. Pool and D.J. Young.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; Railroads; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Le travail déraciné : l'impartition flexible dans la dynamique sociale des entreprises forestières du Québec - Lapointe, Paul-André (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "Le travail déraciné : l'impartition flexible dans la dynamique sociale des entreprises forestières du Québec," by Daniel Mercure.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employees; Forest products; Forest products industry; Labor Unions; Outsourcing; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Seniority and Employment Equity for Women - Legault, Marie-Josée (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "Seniority and Employment Equity for Women," by Louise Dulude.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employment; Labor Unions; Sex discrimination; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Women

Plots, Shots, and Liberal Thoughts: Conspiracy Theory and the Death of Ginger Goodwin - Leier, Mark (James Mark) (Labour / Le Travail, 1997)
Examines longstanding conspiracy theories, as well as the reconsideration of forensic evidence given in Susan Mayse's book, "Ginger: The Life and Death of Albert Goodwin," that the British-born miner and labour activist was murdered by Dominion Police on military orders of the federal government in 1918. Concludes that there was no proof of conspiracy nor was there sufficient evidence to show that the police shooter had intent to murder. Argues, however, that this does not absolve the government and business from culpability since they were responsible for taking Canada into an imperial war - and Goodwin, who opposed conscription and the war, was being pursued by the police for evading conscription.
Keywords: CAMPBELL; Dan; CONSPIRACY; CONSPIRACY theories; Canada; GOODWIN; Albert; LABOUR/LE Travail (Book); LEIER; Mark; SELF-defense (Law)

Things That Never Added Up To Me: Songs of Love, War, Theology, Golf and the Great American Railroad - Leier, Mark (James Mark) (Labour / Le Travail, 1997)
The article reviews the book, "Things That Never Added Up To Me: Songs of Love, War, Theology, Golf and the Great American Railroad," by Al Grierson.
Keywords: BOOKS – Reviews; GRIERSON; Al; Music; Nonfiction; THINGS That Never Added up to Me: Songs of Love; War; Theology; Golf & the Great American Railroad (Book)

Conflits du travail, changement social et politique en France depuis 1950 - Lequin, Jacques-André (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "Conflits du travail, changement social et politique en France depuis 1950," by Monique Borrel.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social conditions & trends; Strikes

Paying the Price of Freedom: Family and Labor among Lima's Slaves, 1800-1854 - Lipsett-Rivera, Sonya (Labour / Le Travail, 1997)
The article reviews the book, "Paying the Price of Freedom: Family and Labor Among Lima's Slaves, 1800-1854," by Christine Hünefeldt.
Keywords: BOOKS – Reviews; HUNEFELDT; Christine; Nonfiction; PAYING the Price of Freedom: Family & Labor Among Lima's Slaves 1800-1854 (Book); Slavery

Bibliography: Recent Publications in Canadian Labour History / Bibliographie : Travaux récents en histoire des classes populaires canadiennes - Lonardo, Michael; Sweeney, Robert C. H. (Labour / Le Travail, 1997)
Compilation of recent English/French publications on Canadian labour history that emphasize the period 1800-1975. Materials pertaining to the post-1975 period may also be included, although more selectively. [See the database, Canadian Labour History, 1976-2009, published at Memorial University of Newfoundland.]

Motives for Profit Sharing: A Study of Canadian Chief Executive Officers - Long, Richard J. (Relations industrielles / Industrial Relations, 1997)
A study seeks to explain why companies do or do not introduce employee profit sharing, through a telephone survey of CEOs at 626 Canadian companies. In addition to examining some of the usual contextual variables, the study goes beyond previous work by directly questioning CEOs about their motives for adopting or not adopting profit sharing, and by including managerial philosophy as a possible factor in their decision-making process. Results indicated that managerial philosophy and company size were the 2 key predictors of incidence or profit sharing. However, the firms most likely to adopt profit sharing in the future were those experiencing a high growth in sales coupled with a low growth in employees. Surprisingly, unionization was not related to either presence of, or intention to implement, profit sharing.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Chief executive officers; Correlation analysis; Executives; Labor Unions; Polls & surveys; Profit sharing plans; Size of enterprise; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies

Northern Sandlots: A Social History of Maritime Baseball - Lorenz, Stacy L. (Labour / Le Travail, 1997)
The article reviews the book, "Northern Sandlots: A Social History of Maritime Baseball," by Colin D. Howell.
Keywords: BASEBALL – History; BOOKS – Reviews; HOWELL; Colin D.; NORTHERN Sandlots: A Social History of Maritime Baseball (Book); Nonfiction

Retirement Plans and Pensions: An Empirical Study - Luchak, Andrew A. (Relations industrielles / Industrial Relations, 1997)
Based on 512 survey respondents, the age at which people voluntarily planned to retire was found to be influenced most strongly by incentives for early retirement embodied in their pension plan. The planned age of retirement was also influenced by the accuracy of information about pension plan features as well as by the respondents' age, gender, health status, and marital status, especially the employment and pension status of the spouse. Implications for public policy and human resource practices of the firm, as well as for implicit contracting are discussed.
Keywords: Age and employment; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Early retirement; Labor Unions; Pension funds; Pension plans; Regression analysis; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies

Canadian Railway Workers and World War I Military Service - MacKinnon, Mary (Labour / Le Travail, 1997)
The article discusses the retention of employee records to keep track of railway workers serving the Canadian armed forces during World War I. It discusses the impact of the war on the Canadian economy, citing how it deepened the depression, how it affected the business performance of railways, including the Canadian Pacific Railway (CPR), and how railway employment fell between 1913 and 1915. It mentions the support given by the railway industry to the war effort which is evident in its collaboration with the metal manufacturing sector in producing shells, as well as its assistance to government efforts to boost munitions production. It also explores how companies monitor employees enlisted to serve the military and how this encouraged them to have an accurate record keeping.
Keywords: Armed forces; CANADIAN Pacific Railway Co.; Canada; RAILROADS – Employees; RECORDS management; WAR – Economic aspects; WEAPONS industry; WORLD War; 1914-1918

Espace social de l'entreprise et logiques d'action ouvrières - Maroy, Christian; Fusulier, Bernard (Relations Industrielles / Industrial Relations, 1997)
Les logiques d'action des ouvriers du secteur industriel à l'endroit de la formation et des changements du travail ne sont pas homogènes. Elles sont tributaires de leurs caractéristiques personnelles mais aussi de leurs positions objectives dans l'espace social des entreprises qui les emploient. Des différences importantes de logiques apparaissent ainsi selon la génération des salariés, selon le moment de leur socialisation initiale au travail, ou selon la longueur de la scolarisation initiale. Mais la position dans l'entreprise intervient également. L'article s'appuie sur une monographie d'un équipementier automobile en Wallonie (Belgique) qui depuis une dizaine d'années développe une politique accentuée de modernisation technique et sociale. Le but de la recherche est de saisir les réactions des salariés à ces politiques managériales, en particulier en ce qui concerne la politique de formation. La recherche s'appuie sur une vingtaine d'interviews de travailleurs d'exécution des deux principaux ateliers et sur une étude statistique et documentaire.
Keywords: Attitudes; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employees; Labor Unions; Organizational change

Résistance et transgression. Études en histoire des femmes au Québec - Marshall, Dominique (Labour / Le Travail, 1997)
The article reviews the book, "Résistance et transgression. . Études en histoire des femmes au Québec," by Andrée Lévesque.

Private Policing and Surveillance of Catholics: Anti-Communism in the Roman Catholic Archdiocese of Toronto, 1920-1960 - Maurutto, Paula (Labour / Le Travail, 1997)
This study examines the private policing and surveillance tactics adopted by the Roman Catholic Archdiocese of Toronto to prevent the spread of communism, particularly within its congregation. Catholic "spies" and informants kept the Church abreast of communist maneuverings in ethnic communities, religious organizations, and on university campuses. An extensive moral and educational campaign was launched by the Church to create a bulwark against the Reds. These actions highlight the historical role of voluntary organizations in the policing of citizens and the maintenance of national security. Policing is redefined as a phenomenon that operated beyond the exclusive domain of the state. The analysis seeks to introduce a broader notion of national security and policing by examining the interplay between public and private institutions.
Keywords: CATHOLICS; Communists; Labor; National security; Ontario; SECURITY management; Toronto (Ont.)

Fantasy, the Bomb, and the Greening of Britain: Romantic Protest, 1945-1980 - Mayer, Jill (Labour / Le Travail, 1997)
The article reviews the book, "Fantasy, the Bomb, and the Greening of Britain: Romantic Protest, 1945-1980," by Meredith Veldman.
Keywords: 20th century; BOOKS – Reviews; FANTASY; the Bomb & the Greening of Britain (Book); GREAT Britain; History; Nonfiction; VELDMAN; Meredith

Ideal Surroundings: Domestic Life in a Working-Class Suburb in the 1920s - McDonald, Robert A.J. (Labour / Le Travail, 1997)
The article reviews the book, "Ideal Surroundings: Domestic Life in a Working-Class Suburb in the 1920s," by Suzanne Morton.
Keywords: BOOKS – Reviews; IDEAL Surroundings: Domestic Life in a Working-Class Suburb in the 1920s (Book); MORTON; Suzanne; Nonfiction; Working class

Clients and Consciousness: Drawing Militancy from Confusion on the Front Lines of the State - McElligott, Greg (Labour / Le Travail, 1997)
This article uses the experience of the Canada Employment and Immigration Union to argue that progressive political action is still possible on the front lines of the state. The CEIU has used client coalitions to defend and transform its membership, and these efforts have been aided by the contradictions of the neoconservative project itself. Union successes have occurred when clients and community groups are on side, real material gains are conceivable, and the issues at stake impinge on the discretionary decisions of frontline workers. Union efforts are seen to constitute a prototypical strategy of "countermanagement," which can establish the foundations for a new, more democratically-accountable state.
Keywords: CONTRADICTION; EMIGRATION & immigration; Employees; Labor; Labor Unions; Skilled labor

Réaliser l'équité salariale; L'équité salariale : mise en oeuvre et enjeux - Mercier, Jacques (Relations industrielles / Industrial Relations, 1997)
The article reviews the books, "Réaliser l'équité salariale," by Alain Gazaille and "L'équité salariale : mise en oeuvre et enjeux," by Marie-Thérèse Chicha.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Equal pay for equal work; Labor Unions; Labor law; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Les conditions difficiles dans les emplois des femmes et les instances gouvernementales en santé et en sécurité du travail - Messing, Karen; Boutin, Sophie (Relations industrielles / Industrial Relations, 1997)
Les femmes participent de plus en plus au marché du travail, mais les normes et pratiques qui s'appliquent à la santé au travail ont été élaborées à un moment où les travailleurs étaient surtout des hommes. En 1990, les secteurs d'activité désignés comme étant les plus prioritaires pour l'intervention par la Commission de la santé et de la sécurité du travail du Québec avaient un taux de masculinité qui s'élevait à plus de 85 %. Dans cet article, nous démontrons une certaine exclusion des femmes de la prévention en santé au travail, nous donnons des explications pour cette exclusion et nous proposons des mesures de correction.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employment; Labor Unions; Laws & regulations; Occupational health & safety; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Women; Working conditions

Fighter with a Heart: Writings of Charles Owen Rice, Pittsburgh Labor Priest - Moran, Martin (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "Fighter with a Heart: Writings of Charles Owen Rice, Pittsburgh Labor Priest," edited by Charles McCollester.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor; Labor Unions; Religion; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Union leadership

Copper and Class Struggle - Mouat, Jeremy (Labour / Le Travail, 1997)
The article reviews and comments on the books "Race and Labor in Western Copper: The Fight for Equality, 1896-1918," by Philip J. Mellinger and "Copper Crucible: How the Arizona Miners' Strike of 1983 Recast Labor-Management Relations in America," by Jonathan D. Rosenblum.
Keywords: BOOKS – Reviews; COPPER Crucible (Book); MELLINGER; Philip J.; Nonfiction; RACE & Labor in Western Copper: The Fight for Equality 1896-1918 (Book); ROSENBLUM; Jonathan D.

The Entrepreneurial Role of Organized Labour in the British Columbia Motion Picture Industry - Murphy, David G. (Relations industrielles / Industrial Relations, 1997)
Research into an industrial sector reflecting principles of the emergent network model of production indicates that organized labor can play a positive role in post-Fordist system of industrial governance. Within the dynamic motion picture industry of British Columbia (B.C.), organized labor was the key organizational factor in the birth and rapid expansion of the agglomeration of small, specialized film production firms. In this process, B.C. film unions have become the dominant actors in forging collaborative relations between local production companies, between the sector and the state, and between the district and other film centers, so critical to the success of the network model.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; Motion picture industry; Roles; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Horses of a Shared Colour: Interpreting Class and Identity in Turn-of-the-Century Vancouver - Nelles, H. V. (Labour / Le Travail, 1997)
The article reviews several books including "Red Flags and Red Tape: The Making of a Labour Bureaucracy," by Mark Leier and "Making Vancouver: Class, Status and Social Boundaries," by Robert A. J. McDonald.
Keywords: BOOKS – Reviews; LEIER; Mark; MAKING Vancouver: Class; Status & Social Boundaries (Book); MCDONALD; Robert A. J.; 1944-; Nonfiction; RED Flags & Red Tape: The Making of a Labour Bureaucracy (Book)

"Unions Aren't Native": The Muckamuck Restaurant Labour Dispute, Vancouver, B.C. (1978-1983) - Nicol, Janet Mary (Labour / Le Travail, 1997)
Examines the roles of organized labour, the employer, the government, and the First Nations community with regard to the protracted labour dispute at the Muckamuck Restaurant in Vancouver, BC that ended in 1983 with the restaurant's closure. The case study draws on archival materials in addition to the author's recollections as a former union organizer and picketer during the strike. Concludes that although the strike had a downside, including the state's failure to protect the all-female First Nations workers from the employer's discriminatory and illegal practices, it was nevertheless significant in several respects.
Keywords: British Columbia; Canada; LABOR organizing; LABOR turnover; Labor Unions; Labor disputes; RESTAURANT employees; VANCOUVER (B.C.)

Imperial Leather: Race, Gender and Sexuality in the Colonial Contest - O'Donnell, Lorraine (Labour / Le Travail, 1997)
The article reviews the book, "Imperial Leather: Race, Gender and Sexuality in the Colonial Contest," by Anne McClintock.
Keywords: BOOKS – Reviews; IMPERIAL Leather: Race; Gender & Sexuality in the Colonial Contest (Book); Imperialism; MCCLINTOCK; Anne; Nonfiction

Quelques arpents d'Amérique. Population, économie, famille au Saguenay, 1838-1971 - Ouellet, Fernand (Labour / Le Travail, 1997)
The article reviews the book, "Quelques arpents d'Amérique. Population, économie, famille au Saguenay, 1838-1971," by Gérard Bouchard.

Ireland Before and After the Famine: Explorations in Economic History, 1800-1925 - Owens, Gary (Labour / Le Travail, 1997)
The article reviews the book, "Ireland Before and After the Famine: Explorations in Economic History, 1800-1925," by Cormac O'Grada.
Keywords: BOOKS – Reviews; FAMINES; IRELAND; IRELAND Before & After the Famine: Explorations in Economic History 1800-1925 (Book); Nonfiction; O Grada; Cormac

Book Notes [39, Spring 1997] - Palmer, Bryan D. (Labour/Le Travail, 1997)
The article briefly reviews "Free Books for All: The Public Library Movement in Ontario, 1850-1930," by Lome Bruce, "The Wages of Slavery: From Chattel Slavery to Wage Labour in Africa, the Caribbean and England ," edited by Michael Twaddle, "Progress Without People: New Technology, Unemployment, and the Message of Resistance," by David F. Noble, "The Workers of Nations: Industrial Relations in a Global Economy," edited by Sanford M. Jacoby, "Labour's High Noon: The Government and the Economy, 1945-1951," edited by Jim Fyrth, "Can Europe Work? Germany and the Reconstruction of Postcommunist Societies," edited by Stephen E. Hanson and Willfried Spohn, "Biographical Dictionary of European Labor Leaders," edited by Thomas Lane, "Peasant Metropolis: Social Identities in Moscow, 1929-1941," by David L. Hoffmann, "Catching the Wave: Workplace Reform in Australia," by John Mathews, and "Everyday Forms of State Formation: Revolution and Negotiation of Rule in Modern Mexico," edited by Gilbert M. Joseph and Daniel Nugent.

Book Notes [40, Fall 1997] - Palmer, Bryan D. (Labour / Le Travail, 1997)
The article briefly reviews "Possible Worlds: Experiments in British Columbia," by AH Brown, "The Crest of the Mountain: The Rise of CUPE Local Five in Hamilton," by Ed Thomas, "Free to All: Carnegie Libraries and American Culture, 1890-1920," by Abigail A. Van Slyck, "North American Auto Unions in Crisis: Lean Production as Contested Terrain," edited by William C. Green and Ernest J. Yanaretla, "Trade Union Politics: American Unions and Economic Change 1960s-1990s," edited by Glenn Perusek and Kent Worcester, "Social Work in Practice," by Gerald A.J. de Montigny, "Engineering Labour: Technical Workers in Comparative Perspective," edited by Peter Meiksins and Chris Smith, "Miners, Unions, and Politics, 1910-1947," edited by lan Campbell, Nina Fishman and David Howell, "Gender and Class in Modern Europe," edited by Laura L. Frader and Sonya O. Rose.

What Do We Need A Union For? The TWUA in the South, 1945-1955 - Palmer, Bryan D. (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "What Do We Need A Union For? The TWUA in the South, 1945-1955," by Timothy J. Minchin.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; History; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Textile Workers of America (TWUA); Textile industry

The Big Sleep: The Malartic Mine Fire of 1947 - Palmer, Bryan D.; Lunn, Robin (Labour / Le Travail, 1997)
Introduces "The Big Sleep" by Jack Timmerman (1915-1953), an unpublished, graphic account of the Malartic Mine Fire of 1947 that resuled in the deaths of 12 miners at the gold mine in northwestern Quebec. Provides a biography of Timmerman, who was working at the mine at the time, as well as framing the disaster in terms of the persistence and frequency of such events.
Keywords: ACCIDENT investigation; Gold mines & mining; INQUESTS; LABOUR/LE Travail (Book); LUNN; Robin; MINE fires; PALMER; Bryan D.; QUEBEC (Province)

The British election: A commentary - Panitch, Leo; Leys, Colin (Labour/Le Travail, 1997)
Critiques the British Labour Party's abandonment of its long-standing commitment to "parliamentary socialism" and the electoral platform of the incoming "New Labour" government of Tony Blair. Concludes that new forms of socialist organization are necessary since the path forward does not lie in transforming the Labour Party.

Local and Regional Response to Global Pressure: The Case of Italy and its Industrial Districts - Papillon, Benoît Mario (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "Local and Regional Response to Global Pressure : The Case of Italy and its Industrial Districts," edited by Francesco Cossentino, Frank Pike and Werner Sengenberger.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Globalization; International relations; Labor Unions; Labor relations; Labor unions; Planning & development; SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z

La sécurité d'emploi dans le secteur public, Essai - Paquet, Renaud (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "La sécurité d'emploi dans le secteur public, Essai," by Louis Borgeat.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Civil service; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

How the 'Reds' Got Their Man: The Communist Party Unmasks an RCMP Spy - Parnaby, Andrew; Kealey, Gregory S. (Labour / Le Travail, 1997)
Documents the exposure of Jack Esselwein, also known as Sergeant John Leopold, who, as an undercover operative of the Royal Canadian Mounted Police, joined the Communist Party of Canada. His identity was revealed after a series of police raids on August 11, 1931, which led to the arrest of a number of leading Communists, including Tim Buck. Esselwein testified at the trial in November 1931 whereby the Communists were convicted and sentenced to penitentiary terms under the notorious section 98 of the criminal code. They had already discovered that Esselwein was a police spy. The Toronto Daily Star report (published November 13, 1931) on Esselwein's unmasking is included in the article.
Keywords: BUCK; Tim; Canada; Communist Party of Canada; ESSELWEIN; Jack; LEOPOLD; John; MALCOLM; Bruce; MCEWEN; Tom; Royal Canadian Mounted Police (RCMP); SPIES

In Search of the Working Class: Essays in American Labor History and Political Culture - Parnaby, Andy (Labour / Le Travail, 1997)
The article reviews the book, "In Search of the Working Class: Essays in American Labor History and Political Culture," by Leon Fink.
Keywords: BOOKS – Reviews; FINK; Leon; IN Search of the Working Class: Essays in American Labor History & Political Culture (Book); Nonfiction; Working class

Reluctant Host: Canada's Response to Immigrant Workers, 1896-1994 - Patrias, Carmela (Labour / Le Travail, 1997)
The article reviews the book, "Reluctant Host: Canada's Response to Immigrant Workers, 1896-1994," by Donald H. Avery.
Keywords: AVERY; Donald H.; BOOKS – Reviews; Foreign workers; Nonfiction; RELUCTANT Host: Canada's Response to Immigrant Workers 1896-1994 (Book)

La flexibilité du travail dans le secteur du textile et de l'habillement en Grèce du Nord - Pelagidis, Theodore (Relations industrielles / Industrial Relations, 1997)
Cette étude a pour objectif la mise en relief des formes et caractéristiques que revêt la flexibilité — du travail principalement — du système productif de l'agglomération de Thessalonique, région connue pour son potentiel et la souplesse de ses structures de production et de travail. La première partie traite des concepts de flexibilité numérique et de flexibilité fonctionnelle dans le cadre de l'entreprise flexible, ainsi que des diverses interprétations qui en ont été faites. Nous utilisons ensuite ces concepts, dans la deuxième partie, pour étudier les caractéristiques de la flexibilité du système de production de l'agglomération de Thessalonique dans ses branches les plus dynamiques, à savoir l'habillement et le textile. L'enquête sur le terrain permet de préciser les traits distinctifs et de dégager la forme de flexibilité qui semble fonder le dynamisme de ce système productif.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employees; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Textile industry

What Impact Has Privatization Had on Pay and Employment?: A Review of the Uk Experience - Pendleton, Andrew (Relations industrielles / Industrial Relations, 1997)
The features and objectives of privatization in the UK are examined. The centrality of labor management and industrial relations objectives to the program are outlined, with particular attention to the capacity of privatization to reduce political influences on pay determination and to encourage labor-shedding improvements in efficiency. The paper than considers the available evidence of the effects of privatization on pay and employment. It is found that pay levels have registered above-average increases since privatization. The evidence on employment reductions is more mixed. It is argued that greater product and labor market competition are necessary if the predicted effects of privatization are to be fully realized.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Efficiency; Employment; Labor Unions; Labor relations; Privatization; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Wages & salaries

Union and Employer Confederation Views on Current Labour Relations in 21 Industrialized Nations - Peterson, Richard B.; Sargent, John (Relations industrielles / Industrial Relations, 1997)
A study reports the results of a cross-sectional mail survey sent to top officials of union and employer confederations in 21 industrialized market economies in Western Europe, North America, and Japan. The results regarding their assessment of the current labor relations situation in their own country show some significant differences related to employer vs. union side and by economic groupings. It is concluded that the relatively stable labor-management relationships during the 1960s and 1970s has apparently given way to greater divergence among the major industrial nations in recent years.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; International; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Trends

Diagnosing Unemployment - Phillips, Paul (Labour / Le Travail, 1997)
The article reviews the book, "Diagnosing Unemployment," by Edmond Malinvaud.
Keywords: BOOKS – Reviews; DIAGNOSING Unemployment (Book); MALINVAUD; Edmond; 1923-2015; Nonfiction; Unemployment

Les Ouvriers, la Patrie et la Révolution Paris 1914-1919 - Piette, Christine (Labour / Le Travail, 1997)
The article reviews the book, "Les Ouvriers, la Patrie et la Révolution Paris 1914-1919," by Jean-Louis Robert.

Between Bargaining and Politics: An Introduction to European Labor Relations - Poole, Michael (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "Between Bargaining and Politics: An Introduction to European Labor Relations," by Hans Slomp.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; Politics; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

The Making of the Indian Working Class: The Case of the Tata Iron and Steel Company, 1880-1946 - Prashad, Vijay (Labour / Le Travail, 1997)
The article reviews the book, "The Making of the Indian Working Class: The Case of the Tata Iron and Steel Company, 1880-1946," by Vinay Bahl.
Keywords: BAHL; Vinay; BOOKS – Reviews; INDIA; MAKING of the Indian Working Class: The Case of the Tata Iron & Steel Co. 1880-1946; The (Book); Nonfiction; Working class

Women of the Commonwealth: Work, Family, and Social Change in Nineteenth-Century Massachusetts - Prentice, Alison (Labour / Le Travail, 1997)
The article reviews the book, "Women of the Commonwealth: Work, Family and Social Change in Nineteenth-Century Massachusetts," edited by Susan L. Porter.
Keywords: BOOKS – Reviews; Nonfiction; PORTER; Susan L.; WOMEN – Employment; WOMEN of the Commonwealth: Work; Family & Social Change in 19th-Century Massachusetts (Book)

Ninety-Nine Days: The Ford Strike in Windsor, 1945 - Pryke, Ken (Labour / Le Travail, 1997)
The article reviews the book, "Ninety-Nine Days: The Ford Strike in Windsor, 1945," by Herb Colling.
Keywords: 99 Days: The Ford Strike in Windsor 1945 (Book); BOOKS – Reviews; COLLING; Herb; Nonfiction; STRIKES & lockouts

Grosse Ile: Canada's Irish Famine Memorial - Quigley, Michael (Labour / Le Travail, 1997)
Documents the horrific conditions at the quarantine station located on Grosse Île, a small island in the St. Lawrence River south of the port of Quebec City, during the Irish famine. In 1847-48, newly arrived Irish immigrants died by the thousands of malnutrition and typhus while under quarantine at Grosse Île. Mass graves were dug at the site for the victims, as had been done for the victims of the cholera epidemic of 1832. Discusses the political and economic plight of Ireland - in particular, the decisions of the governing British elite - that resulted in mass starvation and the exodus overseas. In 1996, the Canadian government recognized Grosse Île as an Irish memorial.
Keywords: CHOLERA; EPIDEMICS; FAMINES; GROSSE Ile (Montmagny; Quebec); LABOUR/LE Travail (Book); MEMORIALS; QUEBEC (Province); QUIGLEY; Michael

On the Line at Subaru Isuzu: The Japanese Model and the American Worker - Rinehart, James W. (Labour / Le Travail, 1997)
The article reviews the book, "On the Line at Subaru Isuzu: The Japanese Model and the American Worker," by Laurie Graham.
Keywords: AUTOMOBILE industry; BOOKS – Reviews; GRAHAM; Laurie; Nonfiction; ON the Line at Subaru Isuzu: The Japanese Model & the American Worker (Book); United States

Économie et société en Acadie, 1850-1950 - Robichaud, Léon (Labour / Le Travail, 1997)
The article reviews the book, "Économie et société en Acadie, 1850-1950," by Jacques Paul Couturier and Phyllis E. Leblanc.

Globalization and the Decline of Social Reform - Sacouman, R. James (Labour / Le Travail, 1997)
The article reviews the book, "Globalization and the Decline of Social Reform," by Gary Teeple.
Keywords: BOOKS – Reviews; GLOBALIZATION & the Decline of Social Reform (Book); Globalization; Nonfiction; TEEPLE; Gary

California Red: A Life in the American Communist Party - Sangster, Joan (Labour / Le Travail, 1997)
The article reviews the book, "California Red: A Life in the American Communist Party," Dorothy Ray Healy and Maurice Isserman.
Keywords: BOOKS – Reviews; CALIFORNIA Red: A Life in the American Communist Party (Book); COMMUNIST parties; HEALY; Dorothy Ray; ISSERMAN; Maurice; Nonfiction

Nationalsozialistische Frauenpolitik vor 1933: Dokumentation - Schade, Rosemarie (Labour / Le Travail, 1997)
The article reviews the book, "Nationalsozialistische Frauenpolitik vor 1933: Dokumentation," edited by Hans-Jurgen Arendt, Sabine Hering and Leonie Wagner.
Keywords: ARENDT; Hans-Jurgen; BOOKS – Reviews; HERING; Sabine; NATIONAL socialism & women; NATIONALSOZIALISTISCHE Frauenpolitik vor 1933: Dokumentation (Book); Nonfiction; WAGNER; Leonie

Selling Free Enterprise: The Business Assault on Labor and Liberalism 1945-1960 - Scheinberg, Stephen J. (Labour / Le Travail, 1997)
The article reviews the book, "Selling Free Enterprise: The Business Assault on Labor and Liberalism 1945-1960," by Elizabeth A. Fones-Wolf.
Keywords: BOOKS – Reviews; FONES-Wolf; Elizabeth A.; Free enterprise; Nonfiction; SELLING Free Enterprise: The Business Assault on Labor & Liberalism 1945-1960 (Book)

Nineteenth-Century Collective Violence: Toward a North American Context - See, Scott W. (Labour / Le Travail, 1997)
The study of collective violence has generally reinforced national stereotypes that Canada is a "Peaceable Kingdom" and that the United States is extraordinarily violent. This article assesses the historiography of collective violence since the 1960s and offers specific suggestions for further exploration into Canada's riotous experiences. Scholars often assume that Canada's collective violence has been infrequent and less destructive than American episodes. Future research – with a focus on nativism, the social legitimacy of the crowd, religious and ethnic conflict, the entrenchment of powerful state institutions, and vigilantism – might prove otherwise. Regardless, Canadian collective violence will be better understood if it is conceptualized in a North Atlantic context.
Keywords: Canada; Historiography; NATIVISM; Riots; VIGILANCE committees; violence

Labor and Community: Mexican Citrus Worker Villages in a Southern California County, 1900-1950 - Seixas, Peter (Labour / Le Travail, 1997)
The article reviews the book, "Labor and Community: Mexican Citrus Worker Villages in a Southern California County, 1900-1950," by Gilbert G. Gonzalez.
Keywords: BOOKS – Reviews; GONZALEZ; Gilbert G.; LABOR & Community: Mexican Citrus Worker Villages in a Southern California County 1900-1950 (Book); Labor; Nonfiction

Information = Note to Readers - Sexton, Jean (Relations industrielles / Industrial Relations, 1997)
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Class, Democracy & Labor in Contemporary Argentina - Sheinin, David (Labour / Le Travail, 1997)
The article reviews the book, "Class, Democracy and Labor in Contemporary Argentina," by Peter Ranis.
Keywords: ARGENTINA – Social conditions – 1983-; BOOKS – Reviews; CLASS; Democracy & Labor in Contemporary Argentina (Book); Nonfiction; RANIS; Peter

Arctic Revolution: Social Change in the Northwest Territories, 1935-1994 - Smith, Donald B. (Labour / Le Travail, 1997)
The article reviews the book "Arctic Revolution: Social Change in the Northwest Territories, 1935-1994," by John David Hamilton.
Keywords: ARCTIC Revolution Social Change in the Northwest Territories 1935-1994 (Book); BOOKS – Reviews; HAMILTON; John David; Nonfiction; Social change

From Artisans to Paupers: Economic Change and Poverty in London, 1790-1870 - Smith, Timothy B. (Labour / Le Travail, 1997)
The article reviews the book, "From Artisans to Paupers: Economic Change and Poverty in London, 1790-1870," by David R. Green.
Keywords: BOOKS – Reviews; FROM Artisans to Paupers: Economic Change & Poverty in London 1790-1870 (Book); GREEN; David R.; Nonfiction; POVERTY

"We Ask for British Justice": Workers and Racial Difference in Late Imperial Britain - Smith, Tori (Labour / Le Travail, 1997)
The article reviews the book, "We Ask for British Justice": Workers and Racial Difference in Late Imperial Britain," by Laura Tabili.
Keywords: BOOKS – Reviews; Nonfiction; Race discrimination; TABILI; Laura; WE Ask for British Justice: Workers & Racial Difference in Late Imperial Britain (Book)

Union Mergers in Hard Times: The View From Five Countries - Solomon, Norman A. (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "Union Mergers in Hard Times: The View From Five Countries," by Gary N. Chaison.
Keywords: Acquisitions & mergers; Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Unnecessary Debts - Spotton, Brenda (Labour / Le Travail, 1997)
The article reviews the book, "Unnecessary Debts," by Lars Osberg and Pierre Fortin.
Keywords: BOOKS – Reviews; DEBT; FORTIN; Pierre; Nonfiction; OSBERG; Lars; UNNECESSARY Debts (Book)

Voracious Idols and Violet Hands: Iconoclasm in Reformation Zurich, Strasbourg and Basel - Stayer, James M. (Labour / Le Travail, 1997)
The article reviews the book, "Voracious Idols and Violet Hands: Iconoclasm in Reformation Zurich, Strasbourg and Basel," by Lee Palmer Wandel.
Keywords: BOOKS – Reviews; ICONOCLASM; Nonfiction; VORACIOUS Idols & Violet Hands: Iconoclasm in Reformation Zurich; Strasbourg & Basel (Book); WANDEL; Lee Palmer

Protecting Women: Labor Legislation in Europe, the United States, and Australia, 1880-1920 - Stewart, Mary Lynn (Labour / Le Travail, 1997)
The article reviews the book ,"Protecting Women: Labor Legislation in Europe, the United States, and Australia, 1880-1920," edited by Ulla Wikander, Alice Kessler-Harris and Jane Lewis.
Keywords: BOOKS – Reviews; KESSLER-Harris; Alice; LEWIS; Jane; Nonfiction; PROTECTING Women: Labor Legislation in Europe; the United States & Australia 1880-1920 (Book); WIKANDER; Ulla; WOMEN – Employment – Law & legislation

Bad Girls and Masked Men: Recent Works on Sexuality in US History - Strange, Carolyn (Labour / Le Travail, 1997)
The article reviews and comments on extensivel on several books including "The Girl Problem: Female Sexual Delinquencies in New York 1900-1930," by Ruth M. Alexander, "Gay New York: Gender, Urban Culture and the Making of the Gay Male World," by George Chauncey, and "Delinquent Daughters: Protecting and Policing Adolescent Female Sexuality in the U.S.," by Mary E. Oden.
Keywords: ALEXANDER; Ruth M.; BOOKS – Reviews; CHAUNCEY; George; DELINQUENT Daughters: Protecting & Policing Adolescent Female Sexuality in the US (Book); GAY New York: Gender; Urban Culture & the Making of the Gay Male World (Book); GIRL Problem: Female Sexual Delinquencies in New York 1900-1930; The (Book); Nonfiction; ODEN; Mary E.

Inside Babylon: The Caribbean Diaspora in Britain - Tabili, Laura (Labour / Le Travail, 1997)
The article reviews the book, "Inside Babylon: The Caribbean Diaspora in Britain," edited by Winston James and Clyde Harris.
Keywords: 20th century; BOOKS – Reviews; GREAT Britain; HARRIS; Clyde; History; INSIDE Babylon: The Caribbean Diaspora in Britain (Book); JAMES; Winston; Nonfiction

People of the Bays and Headlands: Anthropological History and the Fate of Communities in the Unknown Labrador - Thornton, Patricia A. (Labour / Le Travail, 1997)
The article reviews the book, "People of the Bays and Headlands: Anthropological History and the Fate of Communities in the Unknown Labrador," by John C. Kennedy.
Keywords: BOOKS – Reviews; History; KENNEDY; John C.; NEWFOUNDLAND & Labrador; Nonfiction; PEOPLE of the Bays & Headlands: Anthropological History & the Fate of Communities in the Unknown Labrador (Book)

"When our membership awakens": Welfare Work and Canadian Union Activism, 1950-1965 - Tillotson, Shirley (Labour / Le Travail, 1997)
Rather than seeing the mainstream, anti-communist labour leadership in the post-war era as opponents of membership activism and as politically right wing, we might more accurately see them as ideologically-diverse architects of an activism designed to suit the institutional conditions of the new industrial legality in the Cold War era. Labour bureaucrats they indisputably were, but the new regime of industrial relations prompted them to re-examine and to attempt to democratize the basis of their institutional power. Evidence for this thesis is supplied through a study of welfare work and its promoters. Further evidence lies in a survey of idological interpretations of union welfare work and the political uses to which it was put.
Keywords: Anti-communist movements; COLD War; 1945-1989; Civil service; INDUSTRIAL welfare; LABOR laws & legislation; Labor leaders; Social movements

Women Workers and Technological Change in Europe in the Nineteenth and Twentieth Centuries - Tilly, Louise A. (Labour / Le Travail, 1997)
The article reviews the book, "Women Workers and Technological Change in Europe in the Nineteenth and Twentieth Centuries," edited by Gertjan de Groot and Marlou Schrover.
Keywords: BOOKS – Reviews; DE Groot; Gertjan; Nonfiction; SCHROVER; Marlou; WOMEN Workers & Technological Change in Europe in the 19th & 20th Centuries (Book); Women employees

ISO 9000 : une force de management - Todorov, Branimir; Laflamme, Marcel (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "ISO 9000 : une force de management," by Branimir Todorov.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Quality management; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Les secrets de la préparation financière à la retraite - Tremblay, Louis (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "Les secrets de la préparation financière à la retraite," by Louis Ascah.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Retirement planning; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Lawyers Against Labor - Tucker, Eric (Labour / Le Travail, 1997)
The article reviews the book, "Lawyers Against Labor: From Individual Rights to Corporate Liberalism," by Daniel R. Ernst.
Keywords: BOOKS – Reviews; ERNST; Daniel R.; LABOR laws & legislation; LAWYERS Against Labor: From Individual Rights to Corporate Liberalism (Book); Nonfiction

Arvida au Saguenay. Naissance d'une ville industrielle - Vallières, Marc (Labour / Le Travail, 1997)
The article reviews the book, "Arvida au Saguenay: Naissance d'une ville industrielle," by José Igartua.

The Impact of Compressed Workweek on Absenteeism - Venne, Rosemary A. (Relations industrielles / Industrial Relations, 1997)
A study consists of absenteeism measures for a group of prison guards who switched from an 8-hour work day to a 12-hour day compressed workweek (CWW) schedule with absenteeism measures for one year prior to the onset of the schedule and 2 years on the new schedule. Absenteeism data were compared between the CWW group and a comparison group of regular schedule guards and between the pre-CWW and CWW periods. Absenteeism levels were higher for the CWW group compared to the comparison group, and were higher over the CWW period when compared to the pre-CWW period. In the best specified models, those guards on the CWW had higher absenteeism than the comparison group, though the latter difference was not statistically significant.
Keywords: Absenteeism; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Effects; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Working hours; Workweeks

'Cowering Women, Combative Men?': Femininity, Masculinity, and Ethnicity on Strike in Two Southern Ontario Towns, 1964-1966 - Ventresca, Robert A. (Labour / Le Travail, 1997)
In August 1964, the souther Ontario local 523 of the United Electrical and Radio Machine Workers led some 450 female auto-parts workers onto the picket-line. A year later, the same union local led over 1,200 male steelworkers in a strike against the Steel Company of Canada. In both cases, Italian immigrants joined with their non-Italian co-workers in a show of class solidarity. Italian men framed their decision to strike in terms of a manly duty as the family's decision maker and breadwinner; Italian women assumed the role of aggressive labour militant with relative equanimity, while the more outwardly militant Italian men expressed considerable personal uncertainty and fear even while they engaged in a public display of cross-ethnic class solidary. The paper explores how gender, class and ethnicity interact to influence the dynamics of labour militancy in the two strikes, though it also gives due consideration to the structural factors that helped to determine the outcome of both strikes.
Keywords: Canada; Foreign workers; IRON & steel workers; Labor disputes; STRIKES & lockouts; Skilled labor

L'État, l'autonomie collective et le travailleur - Étude comparée du droit italien et du droit français de la représentativité syndicale - Verge, Pierre (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "L'État, l'autonomie collective et le travailleur - Étude comparée du droit italien et du droit français de la représentativité syndicale," by Stamatina Yannakourou.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor law; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Competitive Advantage Through People: Unleashing the Power of the Work Force - Villeneuve, François (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "Competitive Advantage Through People: Unleashing the Power of the Work Force," by Jeffrey Pfeffer.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Competitive advantage; Human resource management; Labor Unions; Labor relations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

Sociologie de l'entreprise et de l'innovation - Vultur, Mircea (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "Sociologie de l'entreprise et de l'innovation," by Norbert Alter.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Organizational behavior; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

The Labour-Management Relationship and Organization Outcomes - Wagar, Terry H. (Relations industrielles / Industrial Relations, 1997)
Based on responses from 752 unionized organizations in Canada, a study examines the association between the quality of labor-management relations and a number of organizations outcomes. The average relationship between an employer and its major bargaining unit was moderately cooperative, with 28% of respondents reporting adversarial relations and 5% indicating a highly cooperative relationship. Results from ordered probit estimation indicated that more favorable organizational outcomes (as measured by management perceptions) were generally associated with a more cooperative relationship between union and management.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Effects; Labor Unions; Labor relations; R&D; Research & development; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies; Unionization

L'État des relations professionnelles : traditions et perspectives de la recherche - Weiss, Dimitri (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "L'État des relations professionnelles : traditions et perspectives de la recherche," edited by Gregor Murray, Marie-Laure Morin and Isabel Da Costa.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Professions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

"From Fordist Worker Resistance to Post-Fordist Capitalist Hegemony?" - Wells, Don (Labour / Le Travail, 1997)
The article reviews and comments extensivley on the books "Capitalism Comes to the Backcountry: The Goodyear Invasion of Napanee," by Bryan Palmer and "Working at Inglis: The Life and Death of Canadian Factory," David Sobel and Susan Meurer.
Keywords: BOOKS – Reviews; CAPITALISM Comes to the Backcountry: The Goodyear Invasion of Napanee (Book); MEURER; Susan; Nonfiction; PALMER; Bryan; SOBEL; David; WORKING at Inglis: The Life & Death of Canadian Factory (Book)

Backing and filling: The 1997 Canadian election - Whitaker, Reginald; Rennie, Richard (Labour/Le Travail, 1997)
Discusses the federal Liberals' majority win under Jean Chrétien and its implications for the other political parties.

Occupational Determinants of Professional Union Membership - White, Frank (Relations industrielles / Industrial Relations, 1997)
Empirical studies of union membership usually group all professionals together in one occupational category. A current study uses a simultaneous equations approach to analyze the union or collective bargaining association membership status of a sample of 9,417 employed Canadian professionals and managers from 16 different occupational groups. The results support the hypothesis that there are significant differences among professions in the probability of their members being in unions or collective bargaining associations. The relative differences are explicable in terms of the characteristics of the professions concerned.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Classification; Collective bargaining; Labor Unions; Memberships; Professionals; Professions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies

Team Toyota: Transplanting the Toyota Culture to the Camry Plant in Kentucky - Wils, Thierry (Relations industrielles / Industrial Relations, 1997)
The article reviews the book, "Team Toyota: Transplanting the Toyota Culture to the Camry Plant in Kentucky," by Terry L. Besser.
Keywords: AUTOMOBILE industry; Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Japanese management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z

On the March: Labour Rebellions in the British Caribbean, 1934-39 - Yelvington, Kevin A. (Labour / Le Travail, 1997)
The article reviews the book, "On the March: Labour Rebellions in the British Caribbean, 1934-1939," by O. Nigel Bolland.
Keywords: BOLLAND; O. Nigel; BOOKS – Reviews; GREAT Britain; Nonfiction; ON the March: Labour Rebellions in the British Caribbean 1934-1939 (Book); STRIKES & lockouts

Autowork - Zieger, Robert H. (Labour / Le Travail, 1997)
The article reviews the book, "Autowork," edited by Robert Asher and Ronald Edsforth.
Keywords: ASHER; Robert; AUTOMOBILE industry workers – United States; AUTOWORK (Book); BOOKS – Reviews; EDSFORTH; Ronald; Nonfiction

Obesity as a Covered Disability Under Employment Discrimination Law: An Analysis of Canadian Approaches - Zwerling, Harris L. (Relations industrielles / Industrial Relations, 1997)
Since the passage of the first anti-discrimination laws in North America, the number of groups of classes protected has slowly expanded to include the disabled. British Columbia is the only jurisdiction in Canada in which obesity per se has been found to be a covered disability. All other Canadian jurisdictions that have explicitly addressed the issue require claimants to prove that their obesity is a disabling condition and has an underlying involuntary medical cause. Despite the reticence of various human rights agencies, there is ample legal basis for including obesity as a covered disability under human rights law.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employment discrimination; HUMAN rights; Labor Unions; Laws & regulations; Legislation; Obesity; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; provinces